2005
DOI: 10.1074/jbc.m505286200
|View full text |Cite
|
Sign up to set email alerts
|

Reduced N-Acetylaspartate Levels in Mice Lacking Aralar, a Brain- and Muscle-type Mitochondrial Aspartate-glutamate Carrier

Abstract: Aralar is a mitochondrial calcium-regulated aspartate-glutamate carrier mainly distributed in brain and skeletal muscle, involved in the transport of aspartate from mitochondria to cytosol, and in the transfer of cytosolic reducing equivalents into mitochondria as a member of the malate-aspartate NADH shuttle. In the present study, we describe the characteristics of aralardeficient (Aralar ؊/؊ ) mice, generated by a gene-trap method, showing no aralar mRNA and protein, and no detectable malate-aspartate shuttl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
193
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(216 citation statements)
references
References 54 publications
(54 reference statements)
14
193
1
3
Order By: Relevance
“…Aralar1 moves aspartate out of mitochondria, and glutamate into mitochondria, and works in conjunction with the enzyme aspartate aminotransferase, which is another integral part of the malate-aspartate shuttle. Results with aralar1 −/− mice also provide support for the bioenergetic role for NAA linked to the aspartatemalate shuttle (Jalil et al, 2005). Aralar1 is the only mitochondrial aspartate-glutamate carrier in the brain, and aralar1 −/− mice lack malate-aspartate shuttle activity, have dramatically reduced brain NAA and aspartate levels, and show reduced neuronal respiration on glutamate plus malate (Jalil et al, 2005).…”
Section: A Model Of Naa Synthesis Linked To Mitochondrial Energetics mentioning
confidence: 59%
See 3 more Smart Citations
“…Aralar1 moves aspartate out of mitochondria, and glutamate into mitochondria, and works in conjunction with the enzyme aspartate aminotransferase, which is another integral part of the malate-aspartate shuttle. Results with aralar1 −/− mice also provide support for the bioenergetic role for NAA linked to the aspartatemalate shuttle (Jalil et al, 2005). Aralar1 is the only mitochondrial aspartate-glutamate carrier in the brain, and aralar1 −/− mice lack malate-aspartate shuttle activity, have dramatically reduced brain NAA and aspartate levels, and show reduced neuronal respiration on glutamate plus malate (Jalil et al, 2005).…”
Section: A Model Of Naa Synthesis Linked To Mitochondrial Energetics mentioning
confidence: 59%
“…It has also been shown that the gene for ASPA, which is expressed strongly in oligodendrocytes in the CNS, is not expressed significantly in the peripheral nervous system (Kirmani et al, 2003), suggesting a specific role for the NAA degrading enzyme in CNS myelination, but not in peripheral myelination mediated by Schwann cells. It is interesting in this regard that aralar1 −/− mice showed reduced levels of galactocerebrocides in the CNS, but not in the PNS, providing further support for a role of NAA-derived acetate in synthesis of specific lipids in the brain, but not in peripheral nerves (Jalil et al, 2005). Further, connexin Cx32 is a gap junction protein expressed in both oligodendrocytes and Schwann cells, and Cx32 mutations are associated with X-linked Charcot-Marie-Tooth disease, a peripheral demyelinating disease in which central myelination is unaffected (Menichella et al, 2003).…”
Section: Central Vs Peripheral Myelinationmentioning
confidence: 94%
See 2 more Smart Citations
“…Both sources of lipid are apparently necessary for achieving the highly regulated lipid composition of myelin upon which optimal function depends. Additional evidence for NAA/ASPA participation in CNS myelinogenesis came from a recent study [33] showing that aralar (−/−) mice lacking the mitochondrial Asp-glutamate carrier have marked reduction of brain NAA along with reduced myelinogenesis. It will be of interest to explore how NAA deficits of the kind reported in several other neurological disorders [34] affect the chemical composition and fine structure of CNS myelin over time.…”
Section: Discussionmentioning
confidence: 99%